Aplikasi Teori Newman: Bagaimana Kesalahan Siswa Dalam Menyelesaikan Permasalahan Geometri 3D? - Dhani N Hendrayanto; Sri Adi Widodo; Zainnur Wijayanto; W Wahmad (Universitas Swadaya Gunung Djati, 2021)
Abstract. One of the low achievement in learning mathematics is caused by students' mistakes in solving math problems. Many studies have stated that geometry is a difficult material because many achievements are below the minimum completeness criteria. In connection with this, the purpose of this study was to determine the types of student errors and the causes of errors in class VIII students in solving mathematical problems in geometry. This research method is descriptive qualitative. The number of participants in this study was 2 people who were selected based on certain reasons. The research data collection techniques were written tests (diagnostic tests) and interviews. The data analysis technique used descriptive techniques. The findings in this study were that students made 4 types of errors based on Newman's theory, namely errors in understanding the meaning of a problem, mistakes in transformation, errors in processing skills and errors in writing the final answer. The causes of student errors include misinterpreting the things being asked, not understanding the concept of geometry. By identifying these student mistakes, the teacher is helped in planning the right lesson so that they can anticipate mistakes that are often made by students.Keywords: Newman’s theory, Errors, Problems of Geometry 3D.